E–H Bond Activation of Ammonia and Water by a Geometrically Constrained Phosphorus(III) Compound. Issue 46 (25th September 2015) - Robinson, Thomas P.; De Rosa, Daniel M.; Aldridge, Simon; Goicoechea, Jose M.
Abstract: The synthesis of a phosphorus(III) compound bearing a N, N ‐bis(3, 5‐di‐ tert ‐butyl‐2‐phenoxy)amide ligand is reported. This species has been found to react with ammonia and water, activating the EH bonds in both substrates by formal oxidative addition to afford the corresponding phosphorus(V) compounds. In the case of water, both OH bonds can be activated, splitting the molecule into its constituent elements. To our knowledge, this is the first example of a compound based on main group elements that sequentially activates water in this manner. Abstract : Divide and conquer : A phosphorus(III) compound bearing a tridentate N, N ‐bis(3, 5‐di‐ tert ‐butyl‐2‐phenoxy)amide ligand is reported. This species has been found to react with ammonia and water activating the EH bonds (E=N and O, respectively) in both substrates to afford the corresponding phosphorus(V) compounds. In the case of water, both OH bonds can be activated.